ALPRAZOLAM: profilo farmacoeconomico nei disturbi d’ansia e da attacchi di panico - Mario Eandi (Farmeconomia: Health Economics and Therapeutic Pathways, 2002)
Alprazolam is a triazolo analog of the 1,4 benzodiazepine class, widely used to treat patients with anxiety disorder, panic attacks and anxiety comorbidity with depressive disorder. Following oral administration, alprazolam is readily absorbed with peack plasma levels in 2 hours; extensive hepatic metabolism occurs and about 80% of the oral dose is excreted by kidney. The main metabolic route is hydroxylation catalyzed by cytochrome P450 3A: alpha-hydroxy alprazolam is partially active. Alprazolam possesses anxiolytic properties similar to other benzodiazepines; however, the triazolo ring confers to alprazolam a peculiar antidepressant and antipanic activity. Anxiety disorder, panic attacks with or without agoraphobia, and mixed anxiety-depressive disorder represent an heavy economic burden to National Health System (NHS) and to society. In the present work the clinical pharmacology and the therapeutic profile of alprazolam are reviewed and analysed under the pharmacoeconomic perspectives of the italian patients, General Practitioners, NHS and society.